The relationship between emotional dimensions of sustainable development among the employees of readymade garments (RMG) - Abdullah, Abdul Rashid; Islam, Ariful (Universiti Putra Malaysia Press, 2019)
Readymade garments (RMG) industry of Bangladesh are lesser revealed to sustainable outlines that originating avoidance related with standard health and safety provisions, labor rights, women safety, child labor, pollution, waste disposal and ground water depletion. Recently there are also several safety hazards by way of fire incidents and building collapses which caused death and injury of thousand or garment workers at Bangladesh. Actually a suitable sustainable development scheme for this industry includes the insights of proper employee involvement based upon what is known (knowledge) and done (behavior). So the study aims to investigate the relationship between knowledge and behavior which reflects the complication between what is in fact known and what is done in case of sustainable issues. The study has used both questionnaire survey and interview procedures on 10 BGMEA registered factories of Chittagong to recognize the connection between knowledge and behavior. The target populace of the study has been limited only to the white collar employees. However, the study identified that employee knowledge and behavior of sustainable development contains a moderate, positive relationship (r=.315, n=150, p<0.0005). The accumulated results can possibly assist both employee and concern industry to explore the critical dynamics to initiate suitable involvement towards sustainable development objectives.